Ultrasound Assisted Bismuth Coated Iron Oxide Nanoparticles For A Potential Dual-Modal Ct/Mr Imaging Contrast Media - Braim, Farhank Saber (2024)
In this study, ultrasound rapidly modified Fe3O4 NPs by coating their surface with Bi NPs, creating unique Fe3O4@Bi composite NPs for computed tomography (CT) scan and magnetic resonance imaging (MRI).